Establishment of a revolving credit fund allows 4,500 dairy farmers in West Java to improve manure management and reduce environmental impacts - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Based on SIDPI research demonstrating best practices for manure management, the dairy cooperative KPSBU Lembang has established a revolving fund for investments in manure management serving 4,500 member farms. This will help farmers to stop the current practice of discharging manure to the environment and overfertilization of farm land, and has potential to reduce greenhouse gas emissions from dairy production by up to 20%.